2005
DOI: 10.1016/j.jpainsymman.2004.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Barriers to Pain Management: The Icelandic Barriers Questionnaire II

Abstract: The Barriers Questionnaire-II (BQ-II) is used to evaluate eight attitudinal barriers to cancer pain management. The purpose of this study was to evaluate the psychometric properties of the Icelandic BQ-II (IBQ-II). Icelandic adults (n=244) completed the IBQ-II, the Brief-Pain-Inventory, and demographic questions. Half the responders were male (52%), and 42.8% had pain on the day of data collection. Participants had a mean (SD) age of 34.73 (11.78) years and education of 15.08 (3.69) years. Factor analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
4
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 57 publications
4
70
4
8
Order By: Relevance
“…In contrast, studies conducted in other countries, including Denmark, 24 China (specifically Hong Kong), 25 Iceland, 26 Jordan, 27 and Lithuania, 28 have reported consistently higher barrier scores than those reported by that first validation study. Those higher scores are consistent with the results of our previous study, which focused on Korean cancer patients.…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast, studies conducted in other countries, including Denmark, 24 China (specifically Hong Kong), 25 Iceland, 26 Jordan, 27 and Lithuania, 28 have reported consistently higher barrier scores than those reported by that first validation study. Those higher scores are consistent with the results of our previous study, which focused on Korean cancer patients.…”
Section: Discussioncontrasting
confidence: 66%
“…14,15,[55][56][57][58] In Turkey, 170 patients with CRP were studied, using a questionnaire. 57 It was found that patients had barriers, mostly in relation to addiction, and to a small extent, physical side effects.…”
mentioning
confidence: 99%
“…[12] Kanser ağrısı bireylerin %80-90'ında farmakolojik tedavilerle etkin bir şekilde tedavi edilebilmesine karşın, pratikte bu oran %30-40 civarında kalmakta ve birçok kanser hastası ağrı çekmektedir. [13] Yaşlılarda kanser ağrısı prevalansı tahminleri sınırlıdır. Yapılan tanımlayıcı çalışmalara göre ağrı insidansı geniş bir varyasyon göstermekte, hem kanser nedeniyle hem de kanser dışı nedenlerden dolayı yaşlılar ağrı yaşamaktadır.…”
Section: Yaşlı Hastalarda Ağrı Prevelansıunclassified